1995
DOI: 10.1128/mr.59.3.325-344.1995
|View full text |Cite
|
Sign up to set email alerts
|

Protein trafficking in kinetoplastid protozoa

Abstract: The kinetoplastid protozoa infect hosts ranging from invertebrates to plants and mammals, causing diseases of medical and economic importance. They are the earliest-branching organisms in eucaryotic evolution to have either mitochondria or peroxisome-like microbodies. Investigation of their protein trafficking enables us to identify characteristics that have been conserved throughout eucaryotic evolution and also reveals how far variations, or alternative mechanisms, are possible. Protein trafficking in kineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 230 publications
(3 reference statements)
2
9
0
1
Order By: Relevance
“…Sleeping sickness, caused by the protozoon Trypanosoma brucei , is considered by the World Health Organization to be one of the main tropical parasitic diseases, in which parasites invade and then freely live in the bloodstream of the mammalian host. , The disease is fatal if left untreated. , Existing chemotherapy has serious drawbacks, including severe side effects, low efficacy, increasing resistance, and no effect on the most virulent form of sleeping sickness caused by T. brucei rhodesiense . Other diseases caused by Trypanosomatidae include leishmaniasis ( Leishmania genus) and Chagas disease ( Trypanosoma cruzi ). , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleeping sickness, caused by the protozoon Trypanosoma brucei , is considered by the World Health Organization to be one of the main tropical parasitic diseases, in which parasites invade and then freely live in the bloodstream of the mammalian host. , The disease is fatal if left untreated. , Existing chemotherapy has serious drawbacks, including severe side effects, low efficacy, increasing resistance, and no effect on the most virulent form of sleeping sickness caused by T. brucei rhodesiense . Other diseases caused by Trypanosomatidae include leishmaniasis ( Leishmania genus) and Chagas disease ( Trypanosoma cruzi ). , …”
Section: Introductionmentioning
confidence: 99%
“…The work presented here focuses on glycolysis in trypanosomes as a target for structure-based drug design. It has been shown that upon going from insect to bloodstream form the parasites become fully dependent on glycolysis for energy production. ,, Inhibiting glycolysis in parasites would be expected to slow their proliferation, as has been shown by Clarkson and Brohn for the combination of salicylhydroxamic acid and glycerol . Since the kinetic parameters for all of the enzymes in the glycolytic pathway in T. brucei are known, it has been possible to simulate parasite glycolytic flux in computro . , Based on the computational result that the presence of a competitive inhibitor of hexokinase at a concentration in the range of 0− K I ( K I is the dissociation equilibrium constant for the E·I complex) has little effect on glycolytic flux, it has been argued that competitive inhibitors of glycolytic enzymes will not be useful for blocking energy production …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the function of mtRNAs in kinetoplastids, synthetic PUF-PIN proteins were designed to target a specific GUUAUUGG sequence in the 3 0 -UTR of the edited transcript of the A6 subunit of the mitochondrial FoF1-ATPase [112]. These PUF-PIN proteins contained an N-terminal MTS from dihydroplipoyl dehydrogenase [118]. An A6-ASRE without a MTS (A6-ASRE (−) ) was used as a control.…”
Section: (C) Targeted Mtrna Nucleasesmentioning
confidence: 99%
“…Na Leishmania, ele tem estrutura similar à observada em células de mamíferos, sendo encontrado entre o núcleo e cinetoplasto na região anterior do parasito (Figura 8). Estudos citoquímicos têm demonstrado a participação do complexo de Golgi no processo de glicosilação de glicoconjugados (Clayton, Häusler & Blattner, 1995).…”
Section: Retículo Endoplasmático E Complexo De Golgiunclassified